Laser light scattering and ultracentrifuge studies on sheep liver cytosolic aldehyde dehydrogenase : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Chemistry at Massey University, New Zealand - Harvey, Jacqueline Jean (Massey University, 1995)
The techniques of laser light scattering and ultracentrifugation were used to investigate the association - dissociation behaviour of sheep liver cytosolic aldehyde dehydrogenase. Diffusion and sedimentation coefficients were obtained by these techniques. The enzyme was studied at pH 7.4, a pH at which the enzyme was in an active, associated form, and also at pH 5.2 where the enzyme was thought to be in an inactive, dissociated form (Buckley et al., 1991). Whilst the gel chromatography results reported in this thesis agreed with those observed by Buckley et al. (1991), laser light scattering and ultracentrifuge results displayed no sign of any dissociation taking place. These results led to the proposition of the existence of a predissociated, inactive state of the enzyme. It was thought that this state was able to be converted back to the associated, active form of the enzyme through use of known methods for preventing dissociation and promoting association and activation of the inactive enzyme, but that this state could also dissociate into a smaller species. Laser light scattering studies were also performed on the enzyme in the presence of Mg2+ or propanal, since these were known to promote association of the enzyme in some instances, as well as inhibit it in other cases (Buckley et al., 1991). It was found that the addition of Mg2+ had no significant effect on the diffusion coefficient of the enzyme, but that the presence of propanal at pH 7.4 promoted large-scale aggregation of the enzyme, whilst having little effect at pH 5.2.
Keywords: Aldehyde dehydrogenase